2004
DOI: 10.1590/s0100-879x2004000600017
|View full text |Cite
|
Sign up to set email alerts
|

Effect of strenuous maternal exercise before and during pregnancy on rat progeny renal function

Abstract: The effects of strenuous exercise before and during pregnancy on the renal function and morphological alterations of the progeny were determined in a study on female Wistar rats. This research was done based on a previous study carried out in our laboratory, which showed morphological alterations in rats submitted to this kind of exercise. As the form is related to the function, the physiological relevance of submitting a pregnant female to a high-intensity exercise training regimen could be explained by the f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
7
0

Year Published

2006
2006
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 16 publications
1
7
0
Order By: Relevance
“…For example, birth weight of pups from treadmill-exercised dams was lower than from nonexercised dams in some studies (18,28,48), and treadmill exercise had no effect on birth weight in others (33). Birth weight of pups from pregnant rats that swam for 60 min/day was lower than (38), whereas birth weight of pups from pregnant rats that swam for only 10 min/day was not different from (1), that of pups from control animals. In addition, exercise during pregnancy may cause stress in experimental animals, providing a major confounder in the interpretation of results.…”
mentioning
confidence: 90%
See 1 more Smart Citation
“…For example, birth weight of pups from treadmill-exercised dams was lower than from nonexercised dams in some studies (18,28,48), and treadmill exercise had no effect on birth weight in others (33). Birth weight of pups from pregnant rats that swam for 60 min/day was lower than (38), whereas birth weight of pups from pregnant rats that swam for only 10 min/day was not different from (1), that of pups from control animals. In addition, exercise during pregnancy may cause stress in experimental animals, providing a major confounder in the interpretation of results.…”
mentioning
confidence: 90%
“…Additionally, neither exercise requires a nox-ious stimulus to the rats. This is in contrast to the treadmill running and swimming extensively described in pregnant rats (31,35,38,40); these exercises often involve noxious stimuli to the animals and are likely to require greater energy use than squat exercise or tower climbing. Previously, we demonstrated that voluntary tower climbing and squat exercise to obtain food are sufficiently strenuous to cause modeling of the tibia in nonpregnant rats without a concomitant rise in fecal corticosterone levels (43), a measure of stress in the rat.…”
mentioning
confidence: 93%
“…Further studies with moderate and high intensity exercise models do not show differences between groups concerning birth weight. On the other hand, different reports show that moderate intensity exercises during pregnancy may increase birth weight, while more intense exercises with high frequency, kept for long periods during this phase, may result in children with low weight (26)(27)(28)(29)(30)(31) .…”
Section: Discussionmentioning
confidence: 97%
“…high or low) may be a more effective option with broader outcomes. Indeed, there is evidence that differing exercise intensities during pregnancy have variable effects on maternal and neonatal health outcomes [41,42].…”
Section: Discussionmentioning
confidence: 99%